2017
DOI: 10.1111/jsr.12524
|View full text |Cite
|
Sign up to set email alerts
|

Night sleep in patients with vegetative state

Abstract: Summary Polysomnographic recording of night sleep was carried out in 15 patients with the diagnosis vegetative state (syn. unresponsive wakefulness syndrome). Sleep scoring was performed by three raters, and confirmed by means of a spectral power analysis of the electroencephalogram, electrooculogram and electromyogram. All patients but one exhibited at least some signs of sleep. In particular, sleep stage N1 was found in 13 patients, N2 in 14 patients, N3 in nine patients, and rapid eye movement sleep in 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
5
27
0
1
Order By: Relevance
“…Six studies with 153 patients were included . Relative risk for signs of covert consciousness suggesting MCS or better with sleep EEG compared to clinical examination was 1.55 (95% CI 1.24 to 1.94; P = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies with 153 patients were included . Relative risk for signs of covert consciousness suggesting MCS or better with sleep EEG compared to clinical examination was 1.55 (95% CI 1.24 to 1.94; P = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…15 Similar relation was observed in DOC-patients, whose sleep recordings revealed spindles, preserved signs of consciousness and had higher chances for recovery. 16 Nevertheless, some researchers have shown that spindles are observed also in unconscious patients, [17][18][19] but the results are ambiguous. 20 Slow wave activity (SWA) defines slow wave sleep (SWS), which relates to stage 3 7 or combined stages 3 and 4.…”
Section: The Aim Of This Studymentioning
confidence: 99%
“…In particular, a study reported that UWS patients with even severe impairment showed residual sleep patterns (including, sometimes, REM sleep), and that the presence of slow-wave sleep was correlated with high Coma Recovery Scale-Revised scores [121]. Similarly, other studies showed a discrimination between DoC categories according to sleep findings [122][123][124][125]. Furthermore, "regular" sleep structure was demonstrated as a good predictor of clinical outcome in sub-acute DoC patients and it was stronger than other known prognostic factors of DoC outcome [126,127].…”
Section: Sleepmentioning
confidence: 93%